Inoculums Preparation and Detoxification Process in Monascus Fermented Rice Production - Marlia Singgih Wibowo; Nur Azizah Fitria; Sri Priatni (Journal of Tropical Life Science, 2016)
Monascus fermented rice (MFR), or angkak are well known for their ability to produce monacolin K, a statin compound that potential as a cholesterol-lowering agent. The objective of the research is to study the inoculum preparation and detoxification process in MFR production. In this study, the inoculum was prepared by cultivated M. purpureus HD001 in YMP, YES, and MSG medium. Rice was inoculated with 10% of inoculum and incubated at 30oC, for 14 days. The growth rate and moisture content of MFR were evaluated in the period from 0 to 14th day. The dried MFR was extracted with ethanol 95%, and the ratio of monacolin K/citrinin was estimated by measuring the absorbances of extract at Î»238 (monacolin K) and Î»500 (citrinin). MFR was detoxified by 0.1% v/v of H2O2, at room temperature for one hour. Monacolin K and citrinin content in MFR extract was analyzed by HPLC. Results showed that the growth of Monascus purpureus HD001 on rice which inoculated by MSG inoculum was faster than YES and YMP inoculum. Maximum growth of M.purpureus occurs on the 8th day. The highest moisture content also enerated by MFR which inoculated by MSG inoculum. Maximum absorbance of monacolin K (l238) of MFR which inoculated by MSG inoculum was obtained on the 8th day. HPLC data showed that detoxification of MFR with 0.1% H2O2 was able to reduce citrinin 58.45% and monacolin K 22.04%. After treatment with 0.1% H2O2, ratio of monacolin K/citrinin in MFR samples was increased 1.87 times when compared to before treatment.